2006
DOI: 10.5032/jae.2006.04001
|View full text |Cite
|
Sign up to set email alerts
|

Content Area Reading Strategies and Textbook Use in Agricultural Education

Abstract: Increasingly, agriscience teachers are called upon to demonstrate their contributions to student achievement in math, science, and reading. This national survey of 216 agriscience teachers investigated the current attitudes and practices related to reading in agriscience. Agriscience teachers generally appreciated reading for personal development and learning, but were in less agreement about allocation of time for reading. Further, teachers agreed that reading was important in agriscience, but were in less ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…All six teachers reported to have students with disabilities in class, thus it was concluded that agriculture teachers did not meet the needs of all their students since Direct Instruction and Strategy Instruction were shown to be effective for students with disabilities (Gregory, McLaughlin, Weber, & Stookey, 2005;Walker, Shippen, Alberto, Houchins, & Cihak, 2005). This conclusion coincides with findings from other studies that agriculture teachers have limited incorporation of reading in the classroom (Park & Osborne, 2006a. As with teachers' limited espoused use of Other Characteristics of Instructional Practice, a lack of preparation and comfort is implied through observations of the teachers' instructional practice.…”
Section: Instructional Practices Of Direct Instruction and Strategy Isupporting
confidence: 79%
See 1 more Smart Citation
“…All six teachers reported to have students with disabilities in class, thus it was concluded that agriculture teachers did not meet the needs of all their students since Direct Instruction and Strategy Instruction were shown to be effective for students with disabilities (Gregory, McLaughlin, Weber, & Stookey, 2005;Walker, Shippen, Alberto, Houchins, & Cihak, 2005). This conclusion coincides with findings from other studies that agriculture teachers have limited incorporation of reading in the classroom (Park & Osborne, 2006a. As with teachers' limited espoused use of Other Characteristics of Instructional Practice, a lack of preparation and comfort is implied through observations of the teachers' instructional practice.…”
Section: Instructional Practices Of Direct Instruction and Strategy Isupporting
confidence: 79%
“…Agriculture teachers' perceptions have been studied pertaining to their use of Strategy Instruction to support reading for the general student population (Park & Osborne, 2006a. While teachers described some use of Strategy Instruction, they expressed a need for development and support in order to consistently increase their implementation of Strategy Instruction in the classroom.…”
Section: Agriculture Teachers' Perceptions Toward Teaching Students Withmentioning
confidence: 99%
“…In order for students to succeed in making decisions within the complex, information-based world, it is vitally important that they possess the ability to create knowledge from text, analyze arguments, propose solutions, and make decisions about real-world issues (Alvermann, 2006;National Governors Association [NGA], 2005). Yet, again, agricultural science teachers do not explicitly instruct students with reading strategies (Park & Osborne, 2006).…”
Section: Problems and Challenges Of Reading Deficienciesmentioning
confidence: 99%
“…However, students seldom expend the time and effort to implement strategies and do so only when directed by teachers (Cuevas, 2003). Teachers in agricultural science education seldom direct students to implement CARS (Park & Osborne, 2006 CARS must be explicit, multiple, and accountable for motivation. Reading strategy instruction provides significant gains, even for higher reading level students.…”
Section: Empirical Research On Reading Strategy Instructionmentioning
confidence: 99%
See 1 more Smart Citation